Transforming Medical Tourism: A Tri Hita Karana-Inspired Framework for Cultural and Holistic Wellness In Bali - Made Ajiswara Laba; I Putu Adi Wibowo; Veronica Aurelie Buntoro; Ayu Putu Githa Maheswari; I Gusti Ayu Intan Pramesti Utami; Laras Nazillah Putri (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Medical tourism has emerged as a global phenomenon, driven by cost-effective healthcare, advanced medical technologies, and the allure of exotic destinations. Bali, Indonesia, renowned for its cultural richness and natural beauty, is a burgeoning hub for medical tourism. However, existing models often prioritize economic benefits over cultural and holistic integration, limiting their sustainability. This study proposes a novel medical tourism model grounded in the Balinese philosophy of Tri Hita Karana, which emphasizes harmony with God (Parahyangan), humans (Pawongan), and nature (Palemahan). Using a systematic literature review based on the PRISMA methodology, we synthesized 45 peer-reviewed studies to develop a culturally sensitive and holistic framework. The findings reveal that integrating spiritual wellness, community-based care, and eco-friendly practices enhances patient satisfaction and aligns with global wellness trends. The proposed model offers a transformative approach to medical tourism by embedding Balinese cultural values into healthcare delivery. This study contributes to the literature by addressing the gap in culturally grounded medical tourism frameworks and provides practical recommendations for stakeholders to implement sustainable, holistic care in Bali. Future research should empirically validate the model’s effectiveness and explore its adaptability in other cultural contexts. This framework not only elevates Bali’s position in the global medical tourism market but also promotes cultural preservation and environmental sustainability. Keywords: Medical tourism, Tri Hita Karana, Holistic Health, Bali.